Criminal Responsibility of Children as Narcotics Sellers (Medan District Court Decision) - Bakkara, Bryant Lapanta; Berutu, Sigar P (Journal Social Civilecial, 2026)
This study discusses criminal liability of children involved as narcotics sellers, based on the analysis of a decision from the Medan District Court. The issues examined include how criminal responsibility is applied to children in narcotics offenses, how the juvenile justice system is implemented, and how judges consider cases involving children as narcotics sellers. This study aims to determine criminal liability, the implementation of the judicial system, and judges' considerations regarding children as narcotics dealers. The research method used is normative juridical, employing a statutory approach and a case approach. The legal materials consist of primary, secondary, and tertiary sources obtained through library research. The data analysis is conducted qualitatively by interpreting relevant legislation and court decisions as the object of study. The results show that criminal responsibility for children as narcotics sellers cannot be equated with adults, as it must consider the child's capacity for responsibility, the element of fault, and possible grounds for justification or excuse. The implementation of the juvenile justice system in narcotics cases provides special procedures through investigation, prosecution, and trial stages, emphasizing diversion and restorative justice, although in practice it still faces various obstacles. Meanwhile, judicial considerations in the Medan District Court decision are not solely based on juridical aspects but also include sociological and philosophical considerations, although in some cases inconsistencies in the application of child protection principles are still found.